Absorption, metabolism and excretion of [14C]-sotorasib in healthy male subjects: characterization of metabolites and a minor albumin-sotorasib conjugate - Vuu, Irene; Dahal, Upendra P.; Wang, Zhe; Shen, Xiaomeng; Rodgers, John; Wahlstrom, Jan; Houk, Brett (Cancer chemotherapy and pharmacology, 2022)
Purpose The objectives of this study were to characterize the absorption, metabolism, and excretion of sotorasib and determine the metabolites present in plasma, urine, and feces in healthy male subjects following a single oral 720 mg dose containing approximately 1 μCi of [ 14 C]-sotorasib. Methods Urine, feces, and plasma were collected post-dose and assayed for total radioactivity and profiled for sotorasib metabolites. Urine and plasma were also assayed for sotorasib pharmacokinetics. In addition, in vitro studies were performed to determine the enzymes responsible for formation of major circulating metabolites and protein adducts in human plasma. Results Sotorasib was rapidly absorbed, with a median time to peak concentration of 0.75 h. Mean t 1/2, z of plasma sotorasib, whole blood total radioactivity, and plasma total radioactivity were 6.35, 174, and 128 h, respectively. The geometric mean cumulative recovery was 80.6%; the majority was excreted in feces (74.4%) with a low percentage excreted in urine (5.81%). M10, sotorasib, and M24 were present at 31.6%, 22.2%, and 13.7% of total radioactivity in plasma extracts, respectively. M10 and sotorasib were present at < 5% of administered radioactivity in urine, while only unchanged sotorasib, at 53% of administered radioactivity, was identified in feces. A sotorasib-albumin adduct was identified in plasma as a minor constituent, consistent with the observed radioactivity profile in plasma/blood. Conclusion Sotorasib metabolism involves nonenzymatic glutathione conjugation, GGT-mediated hydrolysis of glutathione adduct, and direct CYP3A and CYP2C8-mediated oxidation. Elimination of sotorasib is predominantly fecal excretion, suggesting dose reduction is not necessary with renal impairment.